Targeting ocular tissues with intravenously administered aptamers selected by in vivo SELEX - Sonja Korhonen; Katja Stenberg; Umair Seemab; Piia Bartos; Katariina Mäkiniemi; Jørgen Kjems; Daniel Miotto Dupont; Astrid Subrizi (Elsevier, 2024)
Ocular diseases create a significant economic burden and decrease in quality of life worldwide. Drugs and carrier molecules that penetrate ocular tissues after intravenous administration are needed for more efficient and patient-friendly treatment of ocular diseases. Here, ocular barrier-penetrating aptamers were selected through the utilization of in vivo SELEX and intravenous injection in rats. Three aptamers-Apt1, Apt2, and Apt5-were chosen based on their specific accumulation in vascularized ocular tissues and further characterized for their in vivo biodistribution using quantitative reverse-transcription PCR (RT-qPCR). A statistically significant difference between ΔCt values of ocular and control tissues with Apt2 (p < 0.0001) and Apt5 (p < 0.0001) was observed. Interestingly, Apt1 was the most abundant aptamer in the sequencing pool, but it did not show a statistically significant difference in in vivo biodistribution between ocular and control tissues. Overall, this study established a functional in vivo SELEX method for discovering ocular tissue targeting aptamers.